Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fcell.2020.604377
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Induced Cytotoxicity: Effects on Mitochondrial Electron Transport Chain

Abstract: Cadmium (Cd) is a well-known heavy metal and environmental toxicant and pollutant worldwide, being largely present in every kind of item such as plastic (toys), battery, paints, ceramics, contaminated water, air, soil, food, fertilizers, and cigarette smoke. Nowadays, it represents an important research area for the scientific community mainly for its effects on public health. Due to a half-life ranging between 15 and 30 years, Cd owns the ability to accumulate in organs and tissues, exerting deleterious effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 67 publications
(91 reference statements)
1
32
0
Order By: Relevance
“…Linking TCA cycle and electron transport system, SDH catalyzes the oxidation of succinate to fumarate and plays a central role in mitochondrial metabolism (Jardim-Messeder et al, 2015). It has been well documented that SDH is the target of Cd (Belyaeva, 2018;Branca et al, 2020) because of its richness of reactive sulfhydryl group (Jay et al, 1991). The inhibition of SDH activity in low concentration (9 and 27 μg/L) of Cd-treated clams was in agreement with those in Cd-treated oysters (Ivanina et al, 2008).…”
Section: Non-monotonic Metabolic Responses To CDsupporting
confidence: 59%
“…Linking TCA cycle and electron transport system, SDH catalyzes the oxidation of succinate to fumarate and plays a central role in mitochondrial metabolism (Jardim-Messeder et al, 2015). It has been well documented that SDH is the target of Cd (Belyaeva, 2018;Branca et al, 2020) because of its richness of reactive sulfhydryl group (Jay et al, 1991). The inhibition of SDH activity in low concentration (9 and 27 μg/L) of Cd-treated clams was in agreement with those in Cd-treated oysters (Ivanina et al, 2008).…”
Section: Non-monotonic Metabolic Responses To CDsupporting
confidence: 59%
“…Alternatively, the process of mitochondrial energy metabolism is also a vulnerable process in external toxic stimulation (Henchcliffe & Beal, 2008). Some studies showed that mitochondrial membrane permeability and electron transport chain (ETC) are the primary targets of Cd induced mitochondrial dysfunction (Branca, Pacini, et al, 2020). Thus, we tested mitochondrial energy metabolism including mitochondria stress test and glycolysis rate analysis using seahorse XFp Extracellular Flux Analyzer.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure usually occurs in industries involving mining, batteries, pigments, coatings, electroplating and plastic stabilizers. Sources of cadmium exposure include plastic toys, battery, paints, ceramics, contaminated water, air, soil, food, fertilizers, and cigarette smoke [9,10].…”
Section: Introductionmentioning
confidence: 99%